The presence of disease in growing spiny lobster Panulirus spp. in floating net cages at Tanjung Putus Island, Lampung - Sukenda; Lastriliah, Mira; Widanarni, Widanarni; Effendi, Irzal; Hidayatullah, Dendi (Jurnal Akuakultur Indonesia, 2024)
Spiny lobster is a member of crustaceans that has high economic value. The demand for export markets in Asian, European and American countries as well as locally, is quite high with an expensive selling price. However, there are obstacles that often occur in spiny lobster rearing cultivation, namely infectious diseases that will cause high mortality. The purpose of this study was to investigate infectious diseases in rearing spiny lobster Panulirus spp. that were kept in floating net cages at Tanjung Putus, Lampung. The research method involved sampling five spiny lobsters in floating net cages, observation of clinical symptoms, bacterial isolation, identification of bacteria, detection of Milky Hemolymph Disease of Spiny Lobster (MHD-SL) through polymerase chain reaction (PCR) analysis and histopathology. The sampling location was at PT. Saibatin Perikanan Indonesia. The bacteria Vibrio parahaemolyticus and Vibrio alginolyticus were detected. Five lobsters were infected by MHD-SL, characterized by milky white hemolymph. All five lobster samples were positively infected with Milky Hemolymph Disease of Spiny Lobster (MHD-SL) through PCR analysis. Histopathological observations showed pathological microanatomical changes in the lobster hepatopancreas tissue, indicating that the tissue changes, in the form of encapsulation and infiltration were due to Rickettsia-like bacteria (RLB) infection. The management of spiny lobster stocking density, maintenance biosecurity, and increased lobster immunity must be implemented in order to prevent MHD-SL disease in floating net cages. Keywords: bacteria, histopathology, MHD-SL, Panulirus spp. ABSTRAK Lobster merupakan anggota crustacea yang memiliki nilai ekonomis yang tinggi. Permintaan pasar ekspor pada negara Asia, Eropa, dan Amerika maupun lokal cukup tinggi dengan nilai jual yang mahal. Akan tetapi, terdapat kendala yang sering terjadi pada budidaya pembesaran lobster yaitu infeksi penyakit yang akan menyebabkan tingginya mortalitas Tujuan penelitian ini adalah untuk menginvestigasi penyakit infeksi pada pembesaran lobster Panulirus spp. yang dipelihara di keramba jaring apung Tanjung Putus, Lampung. Metode penelitian ini meliputi pengambilan sampel lobster sebanyak lima ekor dalam karamba jarring apung (KJA), pengamatan gejala klinis, isolasi bakteri, identifikasi bakteri, deteksi Milky Hemolymph Disease of Spiny Lobster (MHD-SL) melalui analisis Polymerase Chain Reaction (PCR), dan histopatologi. Lokasi pengambilan sampel di PT. Saibatin Perikanan Indonesia, Lampung. Terdapat bakteri Vibrio parahaemolyticus dan V. alginolyticus. Lima ekor lobster terinfeksi oleh MHD-SL yang ditandai dengan hemolim berwarna putih susu. Lima sampel lobster positif terinfeksi penyakit Milky Hemolymph Disease of Spiny Lobster (MHD-SL) melalui analisis PCR. Hasil pengamatan histopatologi terdapat perubahan mikroanatomi patologi pada jaringan hepatopankreas lobster menunjukkan bahwa adanya perubahan jaringan berupa enkapsulasi dan infiltrasi karena adanya infeksi Rickettsia-like bacteria (RLB). Pengelolaan kepadatan penebaran lobster, biosekuritas pemeliharaan, dan peningkatan imunitas lobster harus ditingkatkan untuk mencegah penyakit MHD-SL di KJA. Kata kunci: bakteri, histopatologi, MHD-SL, Panulirus spp.